2006
DOI: 10.1346/ccmn.2006.0540201
|View full text |Cite
|
Sign up to set email alerts
|

Crystal-Chemical Factors Responsible for the Distribution of Octahedral Cations Over trans- and cis-Sites in Dioctahedral 2:1 Layer Silicates

Abstract: Crystal chemical analysis of various dioctahedral 2:1 phyllosilicates consisting of trans-vacant (tv) and cis-vacant (cv) layers and interstratified cv and tv layers shows that there is compositional control over the distribution of octahedral cations over trans and cis sites. Fe3+ and Mg-rich dioctahedral micas (celadonite, glauconite, leucophyllite and most phengite) occur only as tv varieties. Similarly, the occurrence of tv illites and tv illite fundamental particles in illite-smectite (I-S) does not depen… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

6
67
2

Year Published

2011
2011
2021
2021

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 76 publications
(75 citation statements)
references
References 40 publications
6
67
2
Order By: Relevance
“…M min is the molar mass of clay mineral, n is the number of moles of interlayer water per mole of clay, g is the mass fraction of dehydrated clay in the dehydrated sample (clay + impurities). also concluded in a tendency for Mg cations to avoid the formation of Mg-OH-Mg configurations in dioctahedral phyllosilicates from spectroscopic analyses and mechanistic calculations, although it was not verified for some particular cases, such as Mg-rich montmorillonites (Drits et al, 2006). Therefore, the configurational entropic term for the octahedral layer was calculated by considering a distribution of cations Al 3+ , Fe 3+ and Fe 2+ among two octahedral sites, whereas Mg 2+ was distributed only in one octahedral site.…”
Section: Mass (Mg)mentioning
confidence: 96%
“…M min is the molar mass of clay mineral, n is the number of moles of interlayer water per mole of clay, g is the mass fraction of dehydrated clay in the dehydrated sample (clay + impurities). also concluded in a tendency for Mg cations to avoid the formation of Mg-OH-Mg configurations in dioctahedral phyllosilicates from spectroscopic analyses and mechanistic calculations, although it was not verified for some particular cases, such as Mg-rich montmorillonites (Drits et al, 2006). Therefore, the configurational entropic term for the octahedral layer was calculated by considering a distribution of cations Al 3+ , Fe 3+ and Fe 2+ among two octahedral sites, whereas Mg 2+ was distributed only in one octahedral site.…”
Section: Mass (Mg)mentioning
confidence: 96%
“…j Starting suspension for re-oxidation with oxygen and 4-AcNB corresponds to sample 7 G. k R þ 1:5 ðSi 6:5 FeðIIIÞ 1:5 ÞðFeðIIIÞ 4 ÞO 20 ðOHÞ 4 taken from (Decarreau et al, 2008). end-member of a tetrahedrally charged, iron-rich trans-vacant smectite (total iron content of 33.5 wt%). The main factor governing the formation of cis-and trans-vacant layers is the structural iron content with iron-rich smectites (Fe content >0.6/unit cell) being predominantly trans-vacant while those smectites containing lower amounts of iron (Fe content >0.6/unit cell) are cis-vacant (Drits et al, 2006;Wolters et al, 2009). Thus, iron-rich ferruginous smectite (SWa-1) and Ö lberg montmorillonite (for unit cell composition see Table 1), which contain approximately the same amount of total iron ranging in between the endmembers (12-13 wt%), exhibit both a trans-vacant configuration.…”
Section: Introductionmentioning
confidence: 99%
“…By means of neutron powder diffraction, Redfern [1] studied the VI Mg 21 and VI Al 31 ordering in phengite, finding ordering. For dioctahedral smectites, Drits et al [18] proposed that octahedral cation order-disorder probably had important consequences in the formation of cis-vacant and trans-vacant sheets, and that the pairs MgAOHAMg could favor the formation of cis-vacant montmorillonites. Tunega et al [19] reported quantum-mechanical studies, using plane-wave periodic calculations for different cationic arrangement in supercells, and found the short-range ordering is the usual ordering in dioctahedral phyllosilicates, but the longrange ordering would be difficult in these minerals.…”
mentioning
confidence: 99%